Analisis Penggunaan Media Video Dalam Pembelajaran PPKN Kelas IV SDN Plamongansari 02 - Ummi Khoirun Nisa’; Veryliana Purnamasari; Joko Sulianto (Journal on Education, 2023)
One of the media that supports learning is video, video provides positive things in learning. For this reason, the purpose of this study is to analyze the use of video media in learning PPKn Class IV SDN Plamonngansari 02. This type of research is descriptive qualitative. The subject of this study is the teacher. class and all fourth grade students at SDN Plamongansari 02. Data collection techniques used in this study were interviews and observation. Data analysis techniques used include starting from data collection, data reduction, data presentation and drawing conclusions. From the results of the research that has been done, the results show that from the formative evaluation of PPKn on the meaning and meaning of Bhinneka Tunggal Ika, students who score 80-90 have 18 students in the good category and a percentage of 65% of all students, there are 10 students who get a score of 60-79 with an adequate category and a percentage of 35% of all Class IV students. These results state that during Civics learning using video media students can absorb the material well. From the evaluation results, interviews and observations it can be seen that the use of video media in class IV SDN Plamongansari 02 can foster interest in learning and students' understanding of learning PPKn material. The response from the use of video media in learning received a positive response from students at SDN Plamongansari 02. Even though in its application there were several obstacles faced by the teacher